2003
DOI: 10.1002/pssc.200303139
|View full text |Cite
|
Sign up to set email alerts
|

Electronics and sensors based on pyroelectric AlGaN/GaN heterostructures – Part B: Sensor applications

Abstract: In the present article recent results concerning sensor applications of AlGaN layers and AlGaN/GaN heterostructures are summarized. The piezoresistive effect in piezoelectric AlGaN layers is investigated and the dependence of the piezoresistive gauge factor on the Al content is attributed to the influence of strain induced piezoelectric fields. An enhancement of this effect is observed in AlGaN/GaN heterostructures, resulting in high longitudinal gauge factors.The response of gas sensitive Pt:GaN Schottky diod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 134 publications
(71 citation statements)
references
References 49 publications
0
68
0
Order By: Relevance
“…In addition, the limit of the sensitivity of the thin metal oxide chemo-sensing technology, and in particular the applicability to the particular case of the detection of leaking explosives has to be further assessed. It has been shown that the sensitivity of this type of technology can go up to few parts per million (ppm), providing a wide range sensitivity that allows for identification of organic compounds (Neubecker et al 1997;Eickhoff et al 2003). Nevertheless, the chemical traces of some explosives such as TNT are shown to be made of few parts per billion (ppb) (Rose et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the limit of the sensitivity of the thin metal oxide chemo-sensing technology, and in particular the applicability to the particular case of the detection of leaking explosives has to be further assessed. It has been shown that the sensitivity of this type of technology can go up to few parts per million (ppm), providing a wide range sensitivity that allows for identification of organic compounds (Neubecker et al 1997;Eickhoff et al 2003). Nevertheless, the chemical traces of some explosives such as TNT are shown to be made of few parts per billion (ppb) (Rose et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Both structures are grown on 430 μm sapphire substrates. The heteroepitaxial growth of the group III-nitrides on sapphire substrate allows the application of simple planar device structures [7]. The following AlN buffer layer is necessary as it dramatically improves the surface morphology and crystalline quality of the following undoped-GaN layer [13].…”
Section: Materials Structurementioning
confidence: 99%
“…The following AlN buffer layer is necessary as it dramatically improves the surface morphology and crystalline quality of the following undoped-GaN layer [13]. Furthermore, the thermal expansion of the sapphire substrate is close to that of AlN and AlN is also often used as packaging materials for high temperature sensor [7]. For the bulk structure, Si doped-GaN channel is formed near to the surface of the top layer.…”
Section: Materials Structurementioning
confidence: 99%
See 2 more Smart Citations